1992
DOI: 10.1007/bf00174804
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the marginal contribution of adjustable-rate mortgage selection to termination probabilities in a nested model

Abstract: In this study we measure the marginal contribution of ARMs to termination probabilities. To do this we develop a modified nested-logit model of mortgage selection and termination and identify the role of risk aversity in the selection process. Simulations of termination probabilities under different economic scenarios indicate how ARMs decrease overall portfolio risk through declines in prepayment probabilities which more than offset the increases in default probabilities associated with them.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…In examining relative default and prepayment experience of fixed-rate and adjustable-rate mortgages, Cunningham and Capone (1990) and VanderHoff (1996) find that ARM prepayments are less sensitive to changes in economic conditions than fixed-rate mortgages. Capone and Cunningham (1992) find that expected ARM payment adjustments are the primary factor separating ARM prepayment patterns from fixed-rate mortgage prepayment patterns. All of these studies used data from the 1980s; hence, an additional contribution of our paper is to use more recent ARM performance data.…”
Section: Empirical Prepayment Modelsmentioning
confidence: 82%
“…In examining relative default and prepayment experience of fixed-rate and adjustable-rate mortgages, Cunningham and Capone (1990) and VanderHoff (1996) find that ARM prepayments are less sensitive to changes in economic conditions than fixed-rate mortgages. Capone and Cunningham (1992) find that expected ARM payment adjustments are the primary factor separating ARM prepayment patterns from fixed-rate mortgage prepayment patterns. All of these studies used data from the 1980s; hence, an additional contribution of our paper is to use more recent ARM performance data.…”
Section: Empirical Prepayment Modelsmentioning
confidence: 82%
“…Dhillon et al (1987) and Brueckner and Follain (1988) found that the rate difference between FRM and ARM loans, income level and borrowers' mobility (or expected tenure) are the main factors influencing the choice between FRM and ARM. Many researchers including Cunningham and Capone (1990), Capone and Cunningham (1992), Wallace (1995, 1999), Ambrose and LaCour-Little (2001), Calhoun and Deng (2002), and Ambrose et al (2005) studied ARM terminations. In addition to the drivers of prepayment and default that are common to both FRM and ARM loans, such as housing equity position and interest rate environment, some ARM specific characters affecting mortgage termination rates were identified including the shape of the yield curve, lifetime and periodic rate caps/floors, and rate reset frequency.…”
Section: Introductionmentioning
confidence: 99%
“…Only Cunningham and Capone (1990) and Capone and Cunningham 1992 have developed a framework for comparing the termination behavior of ARMs and FRMs. The results of these studies indicate that, compared to FRMs, ARM prepayment probabilities tend to be lower, while default probabilities are higher.…”
Section: Introductionmentioning
confidence: 99%